Future of Food : Shaping a Climate-Smart Global Food System - World Bank Group (World Bank, Washington, DC, 2015)
The report aims to help improve the productivity and resilience of the current food system, and to make agriculture part of the solution to climate change. It presents compelling evidence and new tools for policymakers, serving as a guide to better address the impacts of a warming climate on agriculture and food production. This report argues that climate-smart agriculture is central to efforts to end extreme poverty by 2030 and boost shared prosperity. The growing body of operational experience implementing Climate-Smart Agriculture (CSA) points to a large spectrum of approaches that deliver productivity and resilience gains alongside lower emissions. This paper advocates for an increasing shift toward securing a triple win by implementing agriculture and food production practices that not only boost productivity but also enhance resilience and lower greenhouse gas emissions (GHG)—the three pillars that form the basis of CSA.